"There is nothing like looking, if you want to find something" – asking questions and searching for answers – the evidence based approach. Issue 2 (29th March 2010) - Haroon, Munib; Phillips, Robert
Abstract : Evidence based medicine (EBM) consists of four separate processes. Asking a clinical question Locating the evidence Appraising and synthesizing the evidence Applying the evidence Most people are familiar with the third step but not so familiar with the first two. Well-designed clinical questions can help clarify in a clinicians mind exactly what information is being sought and also help with the search. This clinical question can be framed around the PICO format. With a well-structured PICO information can then be located in a timely manner using the concept of Haynes's 5 S's and a range of websites including trial registers and meta-search engines.